2011
DOI: 10.1089/ten.tea.2011.0155
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Priming of Synovium-Derived Stem Cells for Cartilage Tissue Engineering

Abstract: This study investigated the potential use of synovium-derived stem cells (SDSCs) as a cell source for cartilage tissue engineering. Harvested SDSCs from juvenile bovine synovium were expanded in culture in the presence (primed) or absence (unprimed) of growth factors (1 ng/mL transforming growth factor-b 1 , 10 ng/mL plateletderived growth factor-bb, and 5 ng/mL basic fibroblast growth factor-2) and subsequently seeded into clinically relevant agarose hydrogel scaffolds. Constructs seeded with growth factor-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 41 publications
3
73
0
Order By: Relevance
“…In this study the withdrawal of TGF-after 21 days did not enhance the subsequent functional development of the engineered construct, consistent with our previous findings (Buckley et al 2010b). A strategy of withdrawing TGF-from the culture media may eventually overcome the problem of diminishing matrix synthesis in long-term culture, but may depend, among other factors, on further optimization of stem cell isolation and expansion conditions (Sampat et al 2011) and the cell seeding density (Huang et al 2009). Another concern is that the long-term culture data presented here could be indicative of some inherent inability of cartilaginous constructs engineered using IFP derived stem cells to generate a fully functional tissue once implanted into a defect, or whether these results are merely a result of suboptimal in vitro culture conditions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study the withdrawal of TGF-after 21 days did not enhance the subsequent functional development of the engineered construct, consistent with our previous findings (Buckley et al 2010b). A strategy of withdrawing TGF-from the culture media may eventually overcome the problem of diminishing matrix synthesis in long-term culture, but may depend, among other factors, on further optimization of stem cell isolation and expansion conditions (Sampat et al 2011) and the cell seeding density (Huang et al 2009). Another concern is that the long-term culture data presented here could be indicative of some inherent inability of cartilaginous constructs engineered using IFP derived stem cells to generate a fully functional tissue once implanted into a defect, or whether these results are merely a result of suboptimal in vitro culture conditions.…”
Section: Discussionsupporting
confidence: 89%
“…One explanation for the failure to retain high levels of proteoglycan within a tissue engineered construct could be the failure to develop a collagenous network capable of retaining these key matrix The temporal profiles of sGAG and collagen release to the media suggest that matrix synthesis peaked shortly before or around day 28 of culture. Cartilage tissue engineering studies using chondrocytes (Byers et al 2008), and more recently synovium derived stem cells (Sampat et al 2011), have demonstrated that withdrawal of TGF-from the media after 2-3 weeks of culture enhances long-term matrix accumulation. In this study the withdrawal of TGF-after 21 days did not enhance the subsequent functional development of the engineered construct, consistent with our previous findings (Buckley et al 2010b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stem cells or multipotent stromal cells (MSCs) isolated from various tissues such as bone marrow [1][2][3][4][5][6][7], subcutaneous fat [8][9][10][11], infrapatellar fat pad (IFP) [6,[12][13][14][15][16][17][18][19][20][21] and synovium [9,[22][23][24][25][26], combined with various scaffolds and hydrogels, have been explored for tissue regeneration. The IFP is a particularly attractive source of MSCs for this type of application as it is easy to access and provides a large number of cells with the potential to generate cartilaginous tissue [12,13,20].…”
Section: Introductionmentioning
confidence: 99%
“…24 Further, when joint-derived stem cells are encapsulated in agarose hydrogels, they generate cartilaginous tissues whose mechanical functionality increases with time in culture. [30][31][32] Therefore, agarose would appear to be a promising material to facilitate both the development of a functional engineered cartilaginous graft in vitro and maintenance of a chondrogenic phenotype in vivo.…”
Section: Introductionmentioning
confidence: 99%